The Influence of Taxpayer Understanding, Taxpayer Awareness, and Perception of Tax Sanctions on Taxpayer Compliance of Earth and Buildings - Beatrix Brigita Tapiory; Widi Dwi Ernawati; Fathimatus Zahro Fazda Oktavia (Politeknik Negeri Malang, 2023)
This research aimed to determine the effect of taxpayer comprehension, taxpayer awareness, and perception of tax sanctions on land and building taxpayer compliance in Malang City. This research used a quantitative approach. Data collection is carried out by distributing questionnaires. The population in this research was land and building taxpayers which are registered in Malang City. The number of research population was 283,451 taxpayers with the sampling technique using simple random sampling and slovin formula. The samples obtained for this study were 100 taxpayers. The data analysis technique used multiple linear analysis. The results of this research indicated that taxpayer comprehension, taxpayer awareness, and the perception of sanctions had a positive significant effect on land and building taxpayer compliance in Malang City. The results also showed that taxpayer comprehension, taxpayer awareness, and the perception of sanctions simultaneously had a positive significant effect on land and building taxpayer compliance in Malang City.